Acute Abdominal Pain as a Result of an Isolated Left Ovarian Vein Thrombosis - Abhay Setia; Farzin Adili; Karl Ludwig; Joerg Herold (Case Reports in Medicine)
Ovarian vein thrombosis (OVT) is a rare thromboembolic condition. It involves the right ovarian vein in 70–80% of cases. The risk factors for the development of OVT are pregnancy or puerperium, hormone therapy with estrogen, recent surgery or hospitalization, malignancy, pelvic inflammatory diseases, thrombophilia and idiopathic OVT. We present a rare case of left OVT in a young, non-pregnant woman in her 30 s. A high degree of suspicion is necessitated in patients with the triad of young-middle-aged female, pain abdomen in lower quadrant and hematuria to diagnose OVT. Contrast enhanced computer tomography (CT-venography) is the diagnostic modality of choice. The patient was initially treated with low molecular weight heparin and then switched to direct oral anticoagulants. At 6-monthsfollow-up the patient was free from any symptoms.